2018
DOI: 10.1111/bjh.15578
|View full text |Cite
|
Sign up to set email alerts
|

Direct role of FLT3 in regulation of early lymphoid progenitors

Abstract: Summary Given that FLT 3 expression is highly restricted on lymphoid progenitors, it is possible that the established role of FLT 3 in the regulation of B and T lymphopoiesis reflects its high expression and role in regulation of lymphoid‐primed multipotent progenitors ( LMPP s) or common lymphoid progenitors ( CLP s). We generated a Flt3 conditional knock‐out ( Flt3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Flt3 fl/fl Vav1-Cre were generated to investigate the role of Flt3 in lymphoid development, prior to lymphoid specification [16]. Consistent with the findings detailed above, the panhematopoietic loss of Flt3 had no effect on HSC.…”
Section: Flt3 Signaling In B Lymphopoiesismentioning
confidence: 59%
See 1 more Smart Citation
“…Flt3 fl/fl Vav1-Cre were generated to investigate the role of Flt3 in lymphoid development, prior to lymphoid specification [16]. Consistent with the findings detailed above, the panhematopoietic loss of Flt3 had no effect on HSC.…”
Section: Flt3 Signaling In B Lymphopoiesismentioning
confidence: 59%
“…An additional role for Flt3 in peripheral B cell homeostasis was suggested in results obtained from mixed radiation chimeras transplanted with fetal liver cells from Flt3 fl/fl Rag1-Cre and wildtype competitor cells. Eight weeks post-transplant the authors found impaired reconstitution of B1a, marginal zone B, and conventional B cells in the peritoneal cavity and spleen of the transplant recipients [16]. Thus, in addition to being a critical regulator of BM B lymphopoiesis, Flt3 signaling plays roles in peripheral B cell maturation and class switch recombination.…”
Section: Regulation Of Peripheral B Development By Flt3/flmentioning
confidence: 97%
“…Expression pattern and conditional knockout mouse studies showed that FLT3 expression is maintained and critical at the pro-B stage, where RAG expression is induced. 39 Therefore, our data highlight how neighbor genes can be involved in a deleterious loop linking gene expression, chromatin structure, and oncogenic activation, suggesting a mechanistic framework for deregulation of ectopic genes by RAG-mediated alterations.…”
Section: Discussionmentioning
confidence: 79%
“…The Flt-3L is an important regulator of lymphopoiesis. Its receptor is expressed on multipotent progenitors and sustained on the earliest B-cell and T-cell progenitors [ 24 , 25 ]. Flt-3L is found as membrane-bound and soluble forms.…”
Section: Discussionmentioning
confidence: 99%